Evaluation of an experimental silage inoculant in laboratory and farm silos using alfalfa and forage sorghum - Bolsen, K.; Smith, R.; Ilg, H.; Fung, Daniel Y. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
An experimental microbial inoculant dramatically increased the speed of pH drop and rate and amount of lactic acid production in alfalfa at both 60 and 90 F storage temperatures. In two trials with forage sorghums, the inoculant did not affect the silage fermentation at 60 F but it did produce small improvements in silages at 90 F. In general, sorghum silages at 60 F fermented slower and had high pH values, lower lactic acid, and higher acetic acid contents than silages at 90 F. The response to the additive in a farm silo trial was not consistent for the criteria measured. Ensiling temperatures, chemical compositions, and dry matter recoveries were similar for control and inoculated silages. However, calves fed treated silage had a 5.9% better feed conversion, which resulted in 4.4 lb more gain per ton of ensiled crop
Keywords: Beef; Silage; Alfalfa; Forage sorghum; Laboratory; Farm silos